Climate-smart actions in agriculture for ensuring zero hunger - Singh, G. P.; Sendhil, R.; Chatrath, Ravish (Indian Farming, 2018)
Alleviating hunger is a top priority for most of the countries, especially developing countries owing to climate change affecting food production. Among sectors, agriculture is the most vulnerable and challenges posed by climate change at the forefront have to be viewed at the grassroots level and it has to be addressed holistically rather than devising or formulating stand alone strategies. To meet the future population food demand, especially by 2030, agriculture has to undergo a rapid transformation which itself will increase the resource damage under the existing agricultural production system. Hence, integrating climate resilience into Indian agriculture and natural resource management gains the focus at the moment. To be effective, the implementation of the initiatives for ‘climate smart actions’ should be done in participatory approach with the local partners, government authorities and community based organizations viz., self-help groups, village cooperatives and farmer producer organizations. The current situation requires an immediate attention and abrupt local knowledge to design the framework for ‘climate-smart actions’ at all levels to achieve the target of ‘zero hunger’ by 2030.